Historical Aspects in the Geological Investigation of Northern Greenland. - Dawes, Peter R.; Haller, John (Meddelelser om Grønland, 1979)
Certain geological maps and photographs, prepared for publication by the late Dr. LAUGE KOCH, are presented here together with an explanatory text. The material stems from the first expeditions that carried out systematic topographical and geological mapping in northern Greenland, viz. the 2nd Thule Expedition 1916-18 and the Bicentenary Jubilee Expedition 1920-23. The latter expedition traversed the entire coast from Melville Bugt around the northern tip of Greenland and into eastern Peary Land. Regrettably the geological results of this expedition were never published in full. Geological map coverage of northern Greenland was planned by KOCH as a series of coloured map sheets to be issued with descriptive texts in Meddelelser om Grønland. Only two, of a series of five, actually were published, in 1929 and 1933; the three outstanding maps, originally in proof print in 1931, are presented here. Several annotated photographs that were to have appeared as figures to illustrate the descriptive texts, are also reproduced. The main significance of the maps and photographs is that they define for the first time the regional outcrop pattern of some of the rock units that became part of the established stratigraphical column of northern Greenland. Of particular importance is the illustration of the Silurian geology and a definition of which rock sequences were actually referred to a given formation. The maps and photographs are valuable reference material and they are essential for a full appraisal of the early ideas about the Silurian geology, as well as in any subdivision and eventual redefinition of the existing Silurian formations.